2008
DOI: 10.1038/ni.1602
|View full text |Cite
|
Sign up to set email alerts
|

Direct proteasome-independent cross-presentation of viral antigen by plasmacytoid dendritic cells on major histocompatibility complex class I

Abstract: Although plasmacytoid dendritic cells (pDCs) respond to virus replication in a non-specific fashion by producing large amounts of type I interferon, a rapid, direct role of pDCs in activating antiviral lymphocytes is less clear. Here we showed that pDCs possess the capacity to rapidly initiate antigenspecific antiviral CD8 + T cell responses. Following virus exposure, pDCs efficiently and rapidly internalized exogenous viral antigens and then presented those antigens on major histocompatibility complex (MHC) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
234
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(239 citation statements)
references
References 41 publications
4
234
1
Order By: Relevance
“…However, for a potent antitumor response, both CD4 + and CD8 + T cell activation is essential. Although human pDCs were previously thought to poorly cross-present exogenous Ag to CD8 + T cells, accumulating evidence now suggests that human pDCs are endowed with an efficient cross-presenting machinery (9)(10)(11)(12)(13)(14). Just recently, we could demonstrate the potency of pDCs in a small cohort of metastatic melanoma patients, in whom vaccination with activated pDCs induced favorable immune responses and significantly extended overall survival (15).…”
mentioning
confidence: 67%
“…However, for a potent antitumor response, both CD4 + and CD8 + T cell activation is essential. Although human pDCs were previously thought to poorly cross-present exogenous Ag to CD8 + T cells, accumulating evidence now suggests that human pDCs are endowed with an efficient cross-presenting machinery (9)(10)(11)(12)(13)(14). Just recently, we could demonstrate the potency of pDCs in a small cohort of metastatic melanoma patients, in whom vaccination with activated pDCs induced favorable immune responses and significantly extended overall survival (15).…”
mentioning
confidence: 67%
“…This is profound, considering the important role type I IFNs play in regulating adaptive immunity to a number of other viral infections and, of particular note here, the dsDNA viruses VV and adenovirus (AdV5), which lack the ability to elicit an adaptive immune response in the absence of type I IFNs (61,62). We therefore propose that the main role of pDCs here is not to provide type I IFNs but to act as antigen-presenting cells (APCs) (13), a property recently shown to involve ligation of TLR7 and TLR9 (35), which are, coincidently, the two same TLRs that we have found to be responsible for innate recognition of FPV (E. L. Lousberg, submitted for publication). In antigen presentation experiments which involved the proliferation of OT-I T cells in vitro and in vivo, we demonstrated that pDCs had an important role in antigen presentation and were in fact responsible for presenting antigen to a significantly greater extent than cDCs when DCs were harvested from a previously immunized mouse and coincubated with OT-I T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in human plasmacytoid DCs, cross-presentation of viral antigen is independent of proteasome digestion, with all processing being performed in the endosomal pathway. 31 In ovalbumin cross-presentation by mouse DC systems, data collectively suggests that processing may occur in either the endosomal or cytosolic/proteasomal pathway, depending on the endocytic route taken (ie, choice of binding to endocytic receptors) and configuration of the antigen (ie, soluble or particulate). 4,15,28,32,33 Our data in human MoDCs now shows that for HCMV pp65, Fc␥R-mediated uptake potentiates crosspresentation in a manner that requires processing both in the endosomal pathway and by the proteasome.…”
Section: Discussionmentioning
confidence: 99%
“…3 Evidence for cytosolic entry of (partly) processed protein, and subsequent proteasome involvement is abundant, 33,36-38 but proteasome-independent routes have been described as well. 31,32 In case of proteasome-dependent cross-presentation, newly formed peptides could enter the ER 39 For personal use only. on May 12, 2018.…”
Section: Differential Antigen Uptake Does Not Explain Increased Crossmentioning
confidence: 99%